ANALISA SISTEM PERANCANGAN PENILAIAN RAPORT SISWA BERORIENTASI OBJEK UML (UNIFIED MODELING LANGUAGE)DI SMK INFORMATIKA SUKMA MANDIRI CILEGON - Tb. Dedy Fu’ady; Waliadi Gunawan (Jurnal Ilmiah Sains dan Teknologi, 2018)
ABSTRACT The administration of education in schools that still use manual systems or the use of file elements takes a relatively long time as the administration is not organized. While educational administration activities are a routine activity that aims to facilitate the process of education in schools. For this reason, a solution is needed in solving this problem, namely by designing an education administration system modeling using UML (Unified Modeling Language) the value of student activities that are currently being worked on is still done manually, even though it is computer-aided, but the application is very simple, which is still using Microsoft Office application packages, such as Ms.Word and Ms.Excel. Not to mention the problem of finding data that has been archived or stored in a computer folder will take a long time to get it. Therefore, the author will try to design an information system for student report cards that are object oriented with UML (Unified Modeling Language) at SMK Informatika Sukma Mandiri.